PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PENGGUNA JASA PAKET TOUR PADA TRAVEL MAHATALLA GRAHA TOUR SAMARINDA - M. Alfiyansyah Putra (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
Arlin, SE, who initially as a sub agent has now developed into a company known in East Kalimantan as a travel company that handles domestic and international travel. This study aims to find out the effect of the relationship of price and service quality variables partially and simultaneously on the Customer Satisfaction of tour package service users in the Mahatalla Graha Tour Samarinda Travel and there is one more dominant variable on the Customer Satisfaction of the tour package service users in the Mahatalla Graha Tour Tour in Samarinda. This research was conducted on the Mahatalla Graha Travel Tour in Samarinda, with quantitative descriptive research type and the sampling technique used is Non Probability Sampling with Purposive sampling technique with a sample size of 120 respondents. From the results of the study that the Price and Service Quality variables partially and Simultaneously have a significant effect on Customer Satisfaction on the Mahatalla Graha Travel Samarinda Tour and Service Quality Variable is the most dominant variable influencing the Customer Satisfaction of Tour package service users on the Mahatalla Graha Tour Samarinda Travel.